Decay kinetics of human immunodeficiency virus-specific effector cytotoxic T lymphocytes after combination antiretroviral therapy. - Ogg, G; Jin, X; Bonhoeffer, S; Moss, P; Nowak, M; Monard, S; Segal, J; Cao, Y; Rowland-Jones, S; Hurley, A; Markowitz, M; Ho, D; et al. (1999)
Little is known of the changes in human immunodeficiency virus type 1 (HIV-1)-specific effector cytotoxic T lymphocytes (CTL) after potent antiretroviral therapy. Using HLA/peptide tetrameric complexes, we show that after starting treatment, there are early rapid fluctuations in the HIV-1-specific CTL response which last 1 to 2 weeks. These fluctuations are followed by an exponential decay (median half-life, 45 days) of HIV-1-specific CTL which continues while viremia remains undetectable. These data have implications for the immunological control of drug-resistant virus.